2016
DOI: 10.1038/srep37416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of the mRNA and miRNA expression profiles in the nascent synthetic allotetraploid Raphanobrassica

Abstract: Raphanobrassica is an allopolyploid species derived from inter-generic hybridization that combines the R genome from R. sativus and the C genome from B. oleracea var. alboglabra. In the present study, we used a high-throughput sequencing method to identify the mRNA and miRNA profiles in Raphanobrassica and its parents. A total of 33,561 mRNAs and 283 miRNAs were detected, 9,209 mRNAs and 134 miRNAs were differentially expressed respectively, 7,633 mRNAs and 39 miRNAs showed ELD expression, 5,219 mRNAs and 57 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…In this study, we compared the length distribution of the sRNAs at the level of the reference genome and the previously reported transcriptome, and identified that the majority of sRNAs in these four libraries were 24 nt in length, followed by 21-nt sRNAs, and, at the previous transcriptome level, the majority of sRNAs were also 21-24 nt in length with a peak at 24 nt, followed by 21 nt, but the proportion of 21-nt sRNAs was lower in PF4 compared with PF2 [28,40]. Similar results have also been reported in other polyploid plants, such as raphanobrassica and rice [54,55]. It has been reported that 24-nt sRNAs can not only promote plant cell division and morphogenesis, but also target DNA methylation to regulate gene expression [56], suggesting that DNA methylation might be related to tetraploid Paulownia phenotypic variations.…”
Section: Dem Target Gene Involved In Epigenetic Alterations That Regusupporting
confidence: 72%
“…In this study, we compared the length distribution of the sRNAs at the level of the reference genome and the previously reported transcriptome, and identified that the majority of sRNAs in these four libraries were 24 nt in length, followed by 21-nt sRNAs, and, at the previous transcriptome level, the majority of sRNAs were also 21-24 nt in length with a peak at 24 nt, followed by 21 nt, but the proportion of 21-nt sRNAs was lower in PF4 compared with PF2 [28,40]. Similar results have also been reported in other polyploid plants, such as raphanobrassica and rice [54,55]. It has been reported that 24-nt sRNAs can not only promote plant cell division and morphogenesis, but also target DNA methylation to regulate gene expression [56], suggesting that DNA methylation might be related to tetraploid Paulownia phenotypic variations.…”
Section: Dem Target Gene Involved In Epigenetic Alterations That Regusupporting
confidence: 72%
“…Similarly, the analysis of 21,081 genes in Citrus limonia autotetraploids revealed less than 1.1% differences in comparison with diploids (Allario et al, ). In contrast, many researchers have observed a more noticeable transcriptomic divergence between allopolyploids and their parents in several plants (Li et al, ; Ye et al, ). Remarkably, here we detected >10% transcriptomic differences as a consequence of hexaploid cytotype formation.…”
Section: Discussionmentioning
confidence: 94%
“…To unravel complex links between candidate miRNAs and unigenes, we proposed a strategy that integrated expression data of DEMs and DEUs to visualize the miRNA‐target interaction network and further discover key miRNAs. Here, we defined coherent miRNA targets as those presenting opposite expression patterns compared with those of the miRNAs, showing that the expression of unigenes was negatively correlated with that of miRNAs (Ye, Wang, & Wang, ). To construct the miRNA‐target interaction network, three separate steps were performed.…”
Section: Methodsmentioning
confidence: 99%
“…In order to build the miRNA-mRNA interaction network, the following method was used, as described in previous studies (Ye et al, 2016 ): A target gene was identified by the direction of change in a pairwise comparison, for example S to C, being the reverse of changes in the miRNAs. The miRNA-mRNAs interaction network was constructed using Cytoscape v2.8.3 software ( http://www.cytoscape.org/ ).…”
Section: Methodsmentioning
confidence: 99%